Characterizing Unusual Spatial Clusters of Male Mental Health Emergencies Occurring During the First National COVID-19 "Lockdown" in the East Midlands Region, UK: A Geospatial Analysis of Ambulance 999 Data. Issue 3 (May 2022) - Moore, Harriet Elizabeth; Hill, Bartholomew; Tanser, Frank; Siriwardena, Aloysius Niroshan; Gussy, Mark; Cutts, Morgan; Spaight, Robert
The widespread psychological effects of contagion mitigation measures associated with the novel coronavirus disease 2019 (COVID-19) are well known. Phases of "lockdown" have increased levels of anxiety and depression globally. Most research uses methods such as self-reporting that highlight the greater impact of the pandemic on the mental health of females. Emergency medical data from ambulance services may be a better reflection of male mental health. We use ambulance data to identify unusual clusters of high rates of male mental health emergencies occurring in the East Midlands of the United Kingdom during the first national "lockdown" and to explore factors that may explain clusters. Analysis of more than 5, 000 cases of male mental health emergencies revealed 19 unusual spatial clusters. Binary logistic regression analysis (χ 2 = 787.22, df = 20, p ≤ .001) identified 16 factors that explained clusters, including proximity to "healthy" features of the physical landscape, urban and rural dynamics, and socioeconomic condition. Our findings suggest that the factors underlying vulnerability of males to severe mental health conditions during "lockdown" vary within and between rural and urban spaces, and that the wider "hinterland" surrounding clusters influences the social and physical access of males to services that facilitate mental health support. Limitations on social engagement to mitigate effects of the pandemic are likely to continue. Our approach could inform delivery of emergency services and the development of community-level services to support vulnerable males during periods of social isolation.